Pemanfaatan Limbah Produksi Biodiesel Buah Bintaro Sebagai Sumber Energi Terbarukan - Muhammah Fathuddin; Eva Kurnia Yulyawan; Djoko Wahyudi (STTI Bontang, 2023)
The development of alternative energy sources is a crucial issue in overcoming energy and environmental challenges in the modern era. One of the efforts to deal with this challenge is to explore the potential for liquid smoke produced from bintaro fruit (Cerbera odollam) waste. This study aims to investigate the process of producing liquid smoke from bintaro fruit seed waste and to analyze the chemical composition of the liquid smoke. The main objective of this research is to assess the potential of liquid smoke from bintaro fruit waste as a sustainable alternative energy source. The research was carried out through a series of laboratory experiments which included the extraction of bintaro fruit seed oil and the conversion of this oil into liquid smoke through a pyrolysis process. The research variable was the temperature of the pyrolysis reactor starting at 300, 400, 500 and 600 oC with 3 kg of treated bintaro fruit raw materials for each variation. The results showed that the highest yield of charcoal product was 1765 grams obtained from a reactor temperature of 400 oC and the production of bio oil tended to increase following the increase in pyrolysis temperature and the highest amount of 190 mL was obtained at a temperature of 600 oC. The results of this study have significant implications for the development of alternative energy sources and organic waste management. In addition, this potential can also provide economic benefits for local communities. Based on the research findings, there is an opportunity for further steps to take advantage of the potential of liquid smoke from bintaro fruit waste as a sustainable and environmentally friendly alternative in meeting future energy needs.